THE ROLE OF INVESTMENT IN RENEWABLE ENERGY IN REDUCING CREATIVE ACCOUNTING PRACTICES IN INDUSTRIAL BANK OF IRAQ - Mohammed Hamid Majeed; Hussein Fadhil Abbas; Jasim Gshayyish Zwaid (Scholar Express Journals, 2025)
The study aimed to explore the role of investment in renewable energy in mitigating creative accounting practices at Industrial Bank. To achieve its objectives and collect the necessary data, the researcher developed a questionnaire comprising 40 items. The study's population included 150 employees, from which a sample of 110 employees was selected
Keywords: Investment in Renewable Energy; Creative Accounting Practices; Industrial Bank